2003
DOI: 10.1046/j.1399-3054.2003.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase change in lily bulblets regenerated in vitro

Abstract: During the development of the lily (Lilium), three phases can be distinguished: the juvenile, the vegetative adult and the flowering phase. Juvenile bulblets sprout with one or a few leaves whereas vegetative adult bulblets sprout with a stem with elongated internodes. The transition to the vegetative adult phase was studied in lily (Lilium × cv. Star Gazer) bulblets regenerating on bulb scale segments in vitro. The phase change was marked by the development of a tunica‐corpus structure in the apical meristem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…Wu and Poethig (2006) showed that phase transition from juvenile to mature is stimulated by a high endogenous sucrose level. This seems to be a general mechanism as the same was found in lily (Langens-Gerrits et al 2003). In the juvenile phase, miR156 is highly expressed and its expression decreases dramatically during vegetative phase change (Wu and Poethig 2006).…”
Section: Etiolationsupporting
confidence: 61%
“…Wu and Poethig (2006) showed that phase transition from juvenile to mature is stimulated by a high endogenous sucrose level. This seems to be a general mechanism as the same was found in lily (Langens-Gerrits et al 2003). In the juvenile phase, miR156 is highly expressed and its expression decreases dramatically during vegetative phase change (Wu and Poethig 2006).…”
Section: Etiolationsupporting
confidence: 61%
“…In addition, sprouting type is directly related to a switch in ontogenetic development from juvenile to adult vegetative ( Figure 6). When bulblets are small (<300 mg), they sprout rosette-type of leaves instead of leaves with a stem (Langens-Gerrits et al, 2003a), so there was no adult vegetative bulb in this study. Therefore, the results from this in vivo study indicate that increasing bulblet size during in vitro culture is the main point of interest for future production.…”
Section: Discussionmentioning
confidence: 87%
“…However, the development rate was the closest between the third and fourth generation in which garlic plants reached the commercial size. Previous studies on in vitro cultured lily bulblets revealed that the transition from juvenile to vegetative adult is characteriz-ed by increased mitotic activity in the apical meristem, followed by stem elongation (Langens-Gerrits et al, 2003). This step was related to weight of the bulblets (Niimi, 1995;Langens-Gerrits et al, 2003) and their size (Matsuo and Arisumi, 1978).…”
Section: Generationmentioning
confidence: 97%
“…Previous studies on in vitro cultured lily bulblets revealed that the transition from juvenile to vegetative adult is characteriz-ed by increased mitotic activity in the apical meristem, followed by stem elongation (Langens-Gerrits et al, 2003). This step was related to weight of the bulblets (Niimi, 1995;Langens-Gerrits et al, 2003) and their size (Matsuo and Arisumi, 1978). It seems that a number of growing seasons are necessary for tissue cultured bulblets to reach the adult and commercial size.…”
Section: Generationmentioning
confidence: 97%